PENGARUH STRATEGI PEMASARAN DAN KUALITAS PRODUK TERHADAP CITRA MEREK SERTA IMPLIKASINYA PADA KEPUTUSAN PEMBELIAN SABUN MANDI SHEVA (STUDI PADA KONSUMEN SABUN MANDI SHEVA DI KOPERASI YAMUGHNI BANDUNG) - Budiyanto Budiyanto; Aang Curatman; Kartono Kartono (ITB AAS Indonesia Surakarta, 2024)
This research aims to test and analyze the influence of marketing strategy variables and product quality on brand image and its implications on purchasing decisions for Sheva bath soap. This research uses primary data by distributing questionnaires via goggle form to Sheva bath soap consumers at the Yamughni Bandung Cooperative with a total of 281 respondents. This research data analysis method uses partial least squares – structural equation modeling (PLS-SEM) with the SmartPLS 4.1 data processing application. The results of this research are that there is a positive and significant influence between marketing strategy and product quality on brand image. There is a positive and significant influence between marketing strategy and product quality on purchasing decisions. Brand image has an insignificant positive effect on purchasing decisions. There is an insignificant influence between marketing strategy and product quality on purchasing decisions through brand image.”